2008
DOI: 10.4238/vol7-2gmr424
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of E-cadherin gene in human neuroepithelial tumors

Abstract: ABSTRACT. Cadherins are cell-to-cell adhesion molecules that play an important role in the establishment of adherent-type junctions by mediating calcium-dependent cellular interactions. The CDH1 gene encodes the transmembrane glycoprotein E-cadherin which is important in maintaining homophilic cell-cell adhesion in epithelial tissues. E-cadherin interacts with catenin proteins to maintain tissue architecture. Structural defects or loss of expression of E-cadherin have been reported as a common feature in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
2
29
1
1
Order By: Relevance
“…Consistent with previous studies which found that E-cadherin expression is a rare event in gliomas [4,16], in the current study the E-cadherin expression was limited to a small number of analyzed cases and a low percentage of positive brain tumor tissue. The relationship between the decreasing expression of E-cadherin and the increasing grade of malignancy observed by other authors [16] was not observed in our study. Similarly to other studies [4,16], the low expression of E-cadherin in glioblastomas was revealed in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies which found that E-cadherin expression is a rare event in gliomas [4,16], in the current study the E-cadherin expression was limited to a small number of analyzed cases and a low percentage of positive brain tumor tissue. The relationship between the decreasing expression of E-cadherin and the increasing grade of malignancy observed by other authors [16] was not observed in our study. Similarly to other studies [4,16], the low expression of E-cadherin in glioblastomas was revealed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between the decreasing expression of E-cadherin and the increasing grade of malignancy observed by other authors [16] was not observed in our study. Similarly to other studies [4,16], the low expression of E-cadherin in glioblastomas was revealed in the present study. Some authors indicate that tumor progression is accompanied by cadherin switching, resulting in down-regulation of E-cadherin and upregulation of N-cadherin and cadherin 11 expression [14,18,26].…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The cell adhesion protein E-cadherin plays a major role in maintaining the structure and function of epithelial tissues. Reduced or null E-cadherin expression has been correlated with infiltrative capacity and metastasis in GC, as well as other types of cancer, such as breast, colorectal, and neuroepithelial tumors (Motta et al, 2008;Abascal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%